Nurse Educators’ Ineffective Coping Mechanisms: Do They Propagate Classroom Incivility? - Pyles, Dr. Michele (Issues and Development in Health Research Vol. 2, 2021)
Background: Nursing student incivility has been explicitly described by research, with evidence that nursing students engage in uncivil behaviours on a routine basis. The role of nurse educators has grown to include not only creative classroom and clinical strategies but also strategies for the management of nursing student incivility. The rise in incivility among nursing students is causing great concern for nurse educators and administrators alike. Stress, like incivility, has been connected to the development of negative coping reactions and has an impact on an individual's view of an uncivil interaction. Methods: A mixed-methods convergent parallel design was used to collect data from 39 nurse educators working at three nursing schools in the southern region of the United States. Creswell [1] described the design as “combining elements of both qualitative and quantitative approaches” (p. 3). The design's convergent method enabled the researcher to collect both quantitative and qualitative data, conduct separate analyses, and compare the results. The method supported the Transactional Model of Stress and Coping [2], which served as the study's foundation. A mixed-methods convergent parallel design was appropriate for this investigation. According to the paradigm, people make an initial assessment of the importance or threat of a stressful situation (e.g., challenging, positive, controllable, stressful, or irrelevant). If the encounter is perceived to be dangerous, a secondary appraisal will occur, activating an individual's coping mechanisms. The design enabled the researcher to identify the coping strategies used by nurse educators, when confronted with uncivil encounters with nursing students. Setting: Three different nursing schools in the southern region of the United States served as the study's location. Sample: The sample was a convenience sample of nurse educators employed at the schools of nursing at the selected universities in the southern United States. Selection criteria required participants to be a nurse educator employed by one of the designated universities' schools of nursing in the southern United States. Procedure for Data Collection: Following receipt of Institutional Review Board approval from all of the selected institutions, a letter was drafted and sent to the deans of the nursing schools at the selected universities, requesting permission to collect data. Following approval from the three study schools, data collection on participants began. Participants were given electronic consent forms and told that completing the surveys meant they were participating voluntarily. Participants were given information about human informed consent and told that there would be no long-term physical effects and minimal (if any) long-term emotional or psychological effects from taking part in the study. When discussing their experiences with nursing student incivility, participants were told that they might experience some emotional distress. The Incivility in Nursing Education Survey-Revised (INE-R) [3], which consists of 24 items on student behaviours, used a Likert-type scale and four open-ended questions to collect data on perceptions of incivility. The participants were not asked for any demographic information. All of the responses were taken in an anonymous manner. The occurrence of themes was examined in the four open-ended questions of the INE-R [3] from the perspective of nurse educators. The themes were then classified into categories, which were then coded to demonstrate the relationship between nurse educators' perceptions of nursing student incivility and their chosen coping responses. Responses from participants were entered into an Excel spreadsheet, which was kept with the researcher and locked in a secure cabinet. Only the researcher had access to the cabinet. The Excel spreadsheet was kept on a password-protected flash drive which was only maintained by the researcher. The Ways of Coping Questionnaire (WCQ) [4] was also linked in the body of an email that was sent to the deans of the three selected universities? schools of nursing for completion by nursing faculty. The questionnaire link was distributed via secure Web-based technology (Survey Monkey). The WCQ [4] used a Likert-type scale to provide responses to 66 items. All responses were collected anonymously, and the information gathered from the respondents was entered into an Excel spreadsheet for compilation. The WCQ [4] data collection process was identical to that of the INE-R [3], and included collecting responses to the 66 items on the questionnaire. All of the responses were entered into an Excel spreadsheet, which was kept with the researcher and locked in a secure cabinet. Only the researcher maintained a key to the cabinet. The Excel spreadsheet was secured on a password protected flash drive maintained only by the researcher. Results: The top three ways to deal with nursing student incivility were daydreaming, evaluating the topic to better comprehend it, and running or exercising. The most uncivil behaviours were considered to include making condescending remarks, discriminating statements, and cheating on exams. Conclusions: A critical barrier in less problem-focused coping was identified among nurse educators confronted with incivility. Programs aimed at combating incivility should be revised to provide additional training and support for faculty, and steps should be taken to safeguard the integrity of the nursing profession.